PENGARUH KOMPETENSI EMOSIONAL DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT UNION PLASTIC INDUSTRIES - rona tanjung; ira yuliana (EQUILIBIRIA, 2020)
This study aims to improve emotional competence on employee performance, as well as improve work competence on employee performance, and improve emotional competence and work discipline on employee performance at PT Union Plastic Industries. This study took 133 samples from 200 employees at PT Union Plastic Industries. Sampling is done using the random sampling method. The analysis used is multiple regression. By using a 0.05 significance level. The results of this study indicate that there is a positive and significant effect between emotional competence and work discipline on employee performance, with a significant level of 0,000 (less than 0.05). Thus it means that hypotheses that state emotional competence and work discipline have an association with employee performance can be accepted. It is estimated that there is significant between the variables of emotional competence and simultaneous coordination of the performance of employees of PT Union Plastic Industries with a value of 89,948 (greater than 3.07), with a significance level of 0,000.